EVALUASI PENGUATAN PENDIDIKAN KARAKTER - Basyaruddin, Nurzula Yenti; Rifma, Rifma (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
Character education is not a new thing anymore in Indonesia. Actually, it has been around for a long time and has become a national culture. The advancement of knowledge has led to the erosion of the character of the nation in general and the character of students in particular. A lot of juvenile delinquency sometimes leads to violence and crime. For this reason, the role of family, environment and school is needed. What teachers can do in shaping student character is to include in the school curriculum implemented in all subjects and become extracurricular activities that must be followed by all students. This research was qualitative based on the philosophy of post positivism where the truth that is examined must be in accordance with the object. Based on observations, many juvenile delinquents are seen by students. They skip school and sit in internet cafes, online games and sometimes ride motorcycles that have no clear purpose. Even more so they are "sold" by their friends.